2018
DOI: 10.1002/npr2.12019
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive behavioral analysis of indoleamine 2,3‐dioxygenase knockout mice

Abstract: Ido1 KO mice did not show any clear behavioral abnormalities under normal conditions. Further studies may be necessary to investigate their behavioral phenotype under inflammatory conditions due to their known roles in inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
(51 reference statements)
0
9
0
Order By: Relevance
“…In this report, we utilized a comprehensive set of well-defined behavioral tests [31][32][33][34][35][36][37][38] and investigated behavioral phenotypes including the sensorimotor functions and the cognitive functions of the Syngap1 −/+ mice generated by Komiyama et al on a C57BL/6J genetic background.…”
Section: Introductionmentioning
confidence: 99%
“…In this report, we utilized a comprehensive set of well-defined behavioral tests [31][32][33][34][35][36][37][38] and investigated behavioral phenotypes including the sensorimotor functions and the cognitive functions of the Syngap1 −/+ mice generated by Komiyama et al on a C57BL/6J genetic background.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, reviewing such data may raise interest to study the inflammatory component of depression by pharmacological and/or genetic manipulation of either the ECS or the KP. Selective exogenous cannabinoids [ 170 , 171 ] and enzyme inhibitors of the KP as well as CBR and KP enzyme knock-out animals are available and widely used to study the function of the ECS and KP [ 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 ]. Applying these tools may reveal the response of each system to one another when manipulated in inflammatory-induced depression.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Bacille Calmette-Guérin (BCG) elicited proinflammatory cytokines, but BCG-induced depressive-like behavior was not induced in ido1 -/-knockout mice [68]. However, another study reported that ido1 -/-knockout mice did not exhibit any significantly diferent behavior, compared to the wild type, in comprehensive behavioral assessments including the domain of cognitive function, negative valance system, motor function, social interaction, and pain sensitivity [69]. Ido2 -/-knockout mice increased exploratory activity during light phase [62].…”
Section: Figurementioning
confidence: 99%